EFFECT OF HYDRAZONES AGAINST INTRACELLULAR AMASTIGOTES OF Leishmania panamensis AND A PARASITIC CYSTEIN PROTEASE - Diana L. MUÑOZ (Universidad de Antioquia, 2009)
In this paper, the synthesis of hydrazones derived from cromano, thiocroman, alkyl and aril hydrazones is described, as well as their leishmanicidal activity and their effect on cysteine proteases from L. (V) panamensis. A series of novel phenylthiochromane and benzyl and naphtyl derivatives are synthesized and evaluated for their cytotoxic and antileishmanial activities. Their effect on parasite cysteine protease is also evaluated. Only phenylthiochromane derivatives display some activity against Leishmania (V) panamensis but all compounds are inactive against parasitic cystein protease. These results may suggest a different mechanism of action for these compounds.